The Magic and Mystery of TRIM65 in Diseases - Zhou, Qinyi; Li, Yuan; Zhou, Zhixiang; Zhou, Yiren; Liu, Yizhou; Liu, Wang; Ma, Xiaofeng (Current Medicinal Chemistry, 2025)
Tripartite-motif protein family member 65 (TRIM65) belongs to the tripartite motif (TRIM) protein family. Its typical structure consists of the RING, B-Box motif, and coiled-coil domains, which are highly conserved at the N-terminus and the variable SPRY domain at the C-terminus. TRIM65 is an E3 ubiquitin ligase that participates in physiological and pathological processes through the ubiquitination pathway, including intracellular signal transduction, protein degradation, cell proliferation, apoptosis, carcinogenesis, autophagy, and phenotypic transformation. Evidence shows that TRIM65 plays a remarkable and obscure role in diseases, including multisystem tumours, neurodegenerative diseases, immune system diseases, and inflammatory diseases. This review is devoted to elaborating on the relationship between TRIM65 and diseases and its pathogenic mechanism, providing a theoretical basis for TRIM65 as a possible pathogenic target of diseases and exploring the possible future research direction of TRIM65 and the challenges it may face.
Keywords: atherosclerosis